#1**+5 **

They are equivalent.

$$\frac{A-P}{P} = \frac{A}{P} - \frac{P}{P} = \frac{A}{P} - 1$$

By the way, these answers are not only equivalent to each other, but also right answers to the question asked.

Guest Mar 16, 2015

#3**+5 **

Let's approach it from the other direction

i = A/P - 1 notice that "1" can be written as P/P

So we have

i = A/P - P/P and since we have a common denominator, we can just write this all over that denominator...so we have....

i = [ A - P ] / P which is exactly the same as the other expression

CPhill
Mar 17, 2015